Defining a taxonomy of Medicare-funded home-based clinical care using claims data - Claire K. Ankuda; Katherine A. Ornstein; Bruce Leff; Subashini Rajagopalan; Bruce Kinosian; Abraham A. Brody; Christine S. Ritchie (BMC, 2023)
Abstract Background As more Americans age in place, it is critical to understand care delivery in the home. However, data on the range of home-based services provided by Medicare is limited. We define a taxonomy of clinical care in the home funded through fee-for-service Medicare and methods to identify receipt of those services. Methods We analyzed Fee-for-service (FFS) Medicare claims data from a nationally-representative cohort of older adults, the National Health and Aging Trends Study (NHATS), to identify home-based clinical care. We included 6,664 NHATS enrollees age ≥ 70 and living in the community, observed an average of 3 times each on claims-linked NHATS surveys. We examined provider and service type of home-based clinical care to identify a taxonomy of 5 types: home-based medical care (physician, physician assistant, or nurse practitioner visits), home-based podiatry, skilled home health care (SHHC), hospice, and other fee-for-service (FFS) home-based care. We further characterized home-based clinical care by detailed care setting and visit types. Results From 2011-2016, 17.8%-20.8% of FFS Medicare beneficiaries age ≥ 70 received Medicare-funded home-based clinical care. SHHC was the most common service (12.8%-16.1%), followed by other FFS home-based care (5.5%-6.5%), home-based medical care (3.2%-3.9%), and hospice (2.6%-3.0%). Examination of the other-FFS home-based care revealed imaging/diagnostics and laboratory testing to be the most common service. Conclusions We define a taxonomy of clinical care provided in the home, serving 1 in 5 FFS Medicare beneficiaries. This approach can be used to identify and address research and clinical care gaps in home-based clinical care delivery.